TINDAK PIDANA PENGELAPAN MOBIL TREVEL (Studi Perkara Nomor 55/Pid.B/2019/PN Kbu) - Agung Wahyudi (Legalita, 2021)
Indonesia is a developing country, the higher the economic needs of the community, the higher the risk of crime. Crime will not go away by itself, Cases of crime are getting increasingly common, and the most common is property crime, which includes embezzlement. of rental cars. There have been many cases of embezzlement of rental cars in big cities, one of which occurred in Kotabumi, North Lampung, embezzlement is a form of action that violates the provisions of Article 372 of the Criminal Code, therefore law enforcement against the crime of embezzlement of rental cars must be completed professionally by the authorities. law enforcers so that the case is revealed and can be completely resolved with justice, as well as for the creation of good and fair law enforcement before the law. Research objectives: 1). To find out how the law enforcement against the crime of embezzlement of rental cars. 2). To determine the elements that prevent law enforcement from enforcing the law. the crime of embezzlement of rental cars. The research method used in this study is normative and empirical and the data collection procedures used are: 1). Literature study by reading books, studying, citing, examining what is obtained from the book literature. 2). Field studies by interviewing resource persons. The results of the author's research are: 1). Law enforcement against the embezzlement of a rental car that it is true that the defendant committed a crime of embezzlement. With various considerations the judge in deciding the sentence for the defendant who then the judge decided a prison sentence of 2 years and 10 months. 2). The inhibiting factors in law enforcement against the crime of embezzlement of rental cars are statutory factors, economic factors.